Ocena ograniczeń decyzji inwestycyjnych otwartych funduszy emerytalnych - Leśna-Wierszołowicz, Elwira (The Evaluation of Investment Decisions Limits of Open Pension Funds, 2009)
The article contains the evaluation of investment limits of open pension funds, proposals of changes in this range and conclusions from the questionnaire. The article also presents the recommendations of changes in range of the investment policy given by the Development Board Working Group of Financial Market in January this year
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2009; Nr 39, T. 2, s. 159-165